PENGUKURAN INDEKS PROFESIONALITAS ASN PUSDIKLAT TENAGA ADMINISTRASI BADAN LITBANG DAN DIKLAT KEMENTERIAN AGAMA - Djubaidah (JENTRE, 2021)
This article examines the achievement of the professionalism index of the state civil apparatus in the Pusdiklat, Balitbang, Education and Training Administration of the Ministry of Religion. ASN professionalism becomes very important as one of the services to the country which is reflected in the form of performance. One of these performance measurements is the professionalism index, which is accompanied by a partial least square (PLS) study, as an index analysis tool. The instrument for measuring the professionalism index refers to the BKN Regulation No. 8 of 2019 with the dimensions of measuring qualifications, competence, performance, and discipline. 2020 has generally reached 86.84 (high category). Likewise for other indicators, namely education, discipline, competence and performance, the highest score is discipline, which is 100, while the lowest is educational qualification which only reaches 72.50 (medium category). Therefore, several researchers have proposed to improve the dimensions of educational qualifications, namely through formal education and training for ASN.